The Political Journey of Tunisia Post-Zine El Abidine Ben Ali: The Role of Secularism in Shaping Tunisia's Political Identity - Lidia Maijar; Adetia Andri (Mahesa Research Center (PT. Mahesa Global Publishing), 2024)
The research explores the role of secularism in shaping the political identity of the state. Through a qualitative approach involving textual analysis and secondary data, this article investigates how the political changes following the Arab Spring revolution have influenced the dynamics of secularism and how Tunisia's political identity has formed as a result. The findings reveal that the conflict between secular and religious forces has become a hallmark of post-revolution politics, with ongoing tensions between those advocating for the sustainability of a secular model and those advocating for religious influence in the political order. The study highlights the complexity of Tunisia's post-revolution political journey, with profound implications for political stability and national identity. In conclusion, the research emphasizes that navigating between revolution and stability requires a deep understanding of the role of secularism in shaping Tunisia's political direction and underscores the importance of dialogue and compromise in achieving a sustainable balance between these two forces.